Peran Pendidikan Agama Islam Dalam Penerapan Toleransi Antar Umat Beragama Di Masyarakat Desa Tebing Linggahara Baru Kecamatan Bilah Barat Kabupaten Labuhanbatu - Rambe Roma; Jailani Syahputra Siregar; Shopiah Anggaini Rambe (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study is essential to conduct because it serves an academic purpose and also contributes practically to promoting social harmony and stability. This type of research is also included in initiatives to record the beneficial impact of religion in the public sphere, which has not yet been thoroughly examined scientifically. This study seeks to identify the impact of Islamic Religious Education on fostering tolerance among worshippers in Tebing Linggahara Baru Village. This study employs a qualitative methodology featuring descriptive techniques, utilizing data gathering tools such as interviews, observations, and analysis of documents. Methods for ensuring data validity with credibility involve triangulation, alongside data analysis that includes data reduction, presentation, and conclusion formulation. The findings of the study indicate that PAI is significant in fostering tolerance among religious groups in Tebing Linggahara Baru Village. Islamic religious education in this village occurs via three methods: informal, formal, and non-formal education. In this village, Muslims make up the majority, and both the Muslims and non-Muslims here consistently uphold tolerance. Islamic religious education acquired by Muslims in their families and schools is effectively implemented in daily life, particularly regarding religious tolerance.